Empowering the registered nurses of tomorrow: Students’ perspectives of a simulation experience for recognising and managing a deteriorating patient - Kelly, Michelle; Forber, J.; Conlon, L.; Roche, M.; Stasa, H. (Churchill Livingstone, 2014)
Background: Recognising and responding to patients who are deteriorating are key aspects to improving outcomes. Simulations provide students with exposure to deteriorating patient scenarios and the role of nurses in such events. The number of programmes seeking to provide best possible simulation experiences is growing exponentially. Robust evaluation of these experiences is crucial to ensure maximum benefit. Objectives: To assess the impact of a deteriorating patient simulation experience on students' technical and communication skills; and to determine if differing study programmes and years of previous nursing experience influenced students' responses and experiences. Methods: A convenience sample of final year nursing students (N = 57) in a medical-surgical course at a large urban university completed a descriptive pre/post simulation survey rating their technical skills and communication abilities in recognising and responding to patient deterioration. Changes in pre/post scores were analysed including influence of study programme (3-year, 2-year Enrolled Nurse, 2-year Graduate Entry); gender; and years nursing experience (beyond course clinical practicum).Results: Statistically significant improvements in post-simulation survey scores were demonstrated for combined student group data. Students with greater years of nursing experience had statistically higher scores than those with less experience in both pre- and post-surveys. Specific improvements were identified for: assessing a deteriorating patient; and in seeking help from the medical officer or external service. Conclusions: All student groups gained benefit in participating in a deteriorating patient simulation. For this group, greater years of prior nursing experience led to higher pre- and post-survey scores. The learning activity provided students an experience of the importance of recognising and responding to an acute situation in a timely manner which may be recalled in subsequent clinical situations.